Desiccation–rehydration measurements in bryophytes: current status and future insights. (10th May 2022) - Morales-Sánchez, José Ángel M; Mark, Kristiina; Souza, João Paulo S; Niinemets, Ülo
Abstract: Desiccation–rehydration experiments have been employed over the years to evaluate desiccation tolerance of bryophytes (Bryophyta, Marchantiophyta, and Anthocerotophyta). Researchers have applied a spectrum of protocols to induce desiccation and subsequent rehydration, and a wide variety of techniques have been used to study desiccation-dependent changes in bryophyte molecular, cellular, physiological, and structural traits, resulting in a multifaceted assortment of information that is challenging to synthesize. We analysed 337 desiccation–rehydration studies, providing information for 351 species, to identify the most frequent methods used, analyse the advances in desiccation studies over the years, and characterize the taxonomic representation of the species assessed. We observed certain similarities across methodologies, but the degree of convergence among the experimental protocols was surprisingly low. Out of 52 bryophyte orders, 40% have not been studied, and data are lacking for multiple remote or difficult to access locations. We conclude that for quantitative interspecific comparisons of desiccation tolerance, rigorous standardization of experimental protocols and measurement techniques, and simultaneous use of an array of experimental techniques are required for a mechanistic insight into the different traits modified in response to desiccation. New studies should also aim to fill gaps in taxonomic, ecological, and spatial coverage of bryophytes. Abstract : Review of current state of the art in desiccation tolerance measurements in bryophytes by a systematic survey of desiccation–rehydration studies and their adopted experimental plans.